Software test estimation tool: comparable with COCOMOII model - Islam, Shaiful; Pathik, Bishwajit Banik; Khan, Manzur H.; Habib, Md Mamun (© 2016 IEEE, 2018)
This conference paper was presented in the IEEE International Conference on Industrial Engineering and Engineering Management, ICVES 2014; Bali; Indonesia; 4 December 2016 through 7 December 2016; [© 2016 IEEE] The conference paper's definite version is available at: http://dx.doi.org/10.1109/IEEM.2016.7797865